Atmospheric circulation modulates the spatial variability of temperature in the Atlantic–Arctic region. (4th March 2019) - Champagne, Olivier; Pohl, Benjamin; McKenzie, Shawn; Buoncristiani, Jean‐François; Bernard, Eric; Joly, Daniel; Tolle, Florian
Abstract : The Arctic region has experienced significant warming during the past two decades with major implications on the cryosphere. The causes of Arctic amplification are still an open question within the scientific community, attracting recent interest. The goal of this study is to quantify the contribution of atmospheric circulation on temperature variability in the Atlantic–Arctic region at decadal to intra‐annual timescales from 1951 to 2014. Daily 20th Century reanalyses geopotential height anomalies at 500 hPa were clustered into different weather regimes to assess their contribution to observed temperature variability. The results show that in winter, 25% of the warming (cooling) in the North Atlantic Ocean (northeastern Canada) is due to temporal decreases of high geopotential anomalies in Greenland. This regime influences air mass migration patterns, bringing less cold (warm) air masses into these regions. Additionally, atmospheric warming or cooling has been attributed to a change in nearby oceanic basin surface conditions because of sea ice decline. In summer, about 15% of the warming observed in Norwegian/Greenland Seas is related to an increase in temporal anticyclonic patterns. This ratio reaches 37% in Norway due to an amplification from downwards solar radiation. This study allows for better understanding how natural climate variability modulates the regional signature of climate change and estimating the uncertainties in climate projections. Abstract : Using weather regimes and temperature fields from the 20th century reanalyses, this study aims to understand the role of atmospheric circulation on the variability of temperature in the Atlantic–Arctic from 1951 to 2014. In winter, 25% of the warming (cooling) in the northern Atlantic Ocean (northeastern Canada) is due to less persistent high geopotential anomalies in Greenland. In summer, 35% of the warming observed in Norway can be attributed to a regional increase of geopotential anomalies.